Culturally proficient collaboration : use and misuse of school counselors - Stephens, Diana L.; Lindsey, Randall B. (Thousand Oaks, Calif. : Corwin Press, 2011)
'This book provides a conceptual framework and practical protocols for recognizing school counselors as change agents for school improvement and equity advocates for all students'-- Provided by publisher.
'Although it has become quite common for school counselors to participate in school leadership teams, their role is frequently misunderstood and even misused. In fact, counselors are frequently miscast as'gatekeepers' of the status quo, rather than changes agent for school improvement. The authors of this book believe that 21st century professional school counselors have a primary role in ensuring equitable resources and opportunities for all demographic groups in schools. Culturally Proficient Collaboration provides a conceptual framework and practical protocols to use to understand the roles, responsibilities, and benefits of school counselors functioning as leadership team members. and reflective activities and instruments for readers to use in developing their own skill in serving as leaders, advocates, collaborators, and systemic change agents in creating comprehensive, developmental, results-based school counseling programs for all stakeholders in P-12 schools'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Educational counseling; Student counselors -- Professional relationships; Cross-cultural counseling